(untitled) (Studia Politica. Romanian Political Science Review, 2025)
This edited volume stems from the public debate initiated by the Movement for the Development of Moldova (Mișcarea pentru dezvoltarea Moldovei) on how the development gap affecting the eastern part of Romania can be addressed via territorial reform.2 The contributors to the volume are professors and researchers at the Alexandru Ioan Cuza University of Iași, and at the Romanian Academy in Iași. They are joined by three other colleagues working in Bolzano, Sibiu, and Cluj-Napoca. The contributors cover a broad range of fields: legal studies, geography, sociology, political science, economics, history, ethnology, and linguistics. This provides for a variety of perspectives on regionalism and the territorial and administrative reforms designed to address it. At the same time, as will be shown later, this also creates some issues regarding the coherence of the book.